Guided waves for monitoring setting of conventional and non- vibrated concrete - Jain, Preeti (My University, 2012)
At early ages of concrete structures,strength monitoring is important to determine the structure’s readiness for service. Concrete setting and hardening process are the most critical phases during construction works, influencing to properties of concrete structure, so the application of efficiency non-destructive test methods for early age concrete properties determination is crucial. In this study, apart from standardized methods like Penetration Vicat methods to study the setting of concrete, ultrasonic pulse velocity and suitability of ultrasonic guided waves methods for young concrete characterization is also explored. In ultrasonic method, guided wave is transmitted and received through a waveguide that is embedded in early age concrete. As the cementitious material sets and hardens, the strength of the received waves changes, indicating the transition from semi-fluid to solid state. This thesis proposes to use pulse transmission and pulse echo systems for monitoring setting and hardening phase change in conventional and self compacting concrete.This approach monitors the attenuation of the fundamental guided longitudinal wave mode, resulting from the leakage of energy from the cylindrical steel rod to the surrounding cementitious material. The evolution of the material’s properties is related to the energy leakage or attenuation of the guided wave. The use of guided waves for monitoring setting properties of conventional concrete and non-vibrated (SCC) is presented in this work. The comparison in the setting process of two most commonly used concrete i.e. conventional and non-vibrated concrete is made in the research.
Master of Engineering(Structures)
Keywords: Guided Waves; concrete; health; monitoring